Surfactant‐Assisted Aqueous Extraction Processing of Camellia Seed Oil by Cyclic Utilization of Aqueous Phase. Issue 7 (20th May 2019) - Zhang, Shiqi; Zhang, Wenbin; Liu, Junjun; Zhao, Wei; Yang, Ruijin
Abstract : Tea saponin, an abundant nonionic surfactant in Camellia seeds, is proved to be able to reduce the interfacial tension between oil and water. The tendency of oil transfer from raw material into the aqueous phase is enhanced with the lowering of interfacial tension. Based on the result above, an improved surfactant‐assisted aqueous extraction processing method (SAEP) is established. SAEP can accumulate tea saponin in aqueous phase by the continuous reuse of extracting agent and sequentially reduce the difficulty of oil extraction. Attributed to the decrease in sediment phase (3.09 and 4.96%, respectively, when distilled water and ethanol are used as extracting agents), highest oil yields of 93.58 and 89.62% are obtained, respectively. In addition, the by‐products accumulated continuously in aqueous phase are beneficial for the recycling. The proposed method can save 60–70% of the extracting agent dosage compared with traditional aqueous extraction processing (AEP), which greatly reduces the production cost and wastewater output. Practical Applications : Alcohol‐assisted aqueous extraction processing of Camellia seed oil has been industrialized in China. However, economic benefit of this process is limited by large amount of alcohol consumption and production safety requirements. Surfactant‐assisted aqueous extraction processing (SAEP) accumulates the tea saponin rich in Camellia seeds by the extracting agent recycling use. The high concentration of tea saponin reduces the interfacial tension between oil and water, ensures the extraction rate, and reduces the consumption of the extracting agent. SAEP with a strong operability has the potential to help enterprises improve production process and reduce cost. Tea saponin (TS), which is rich in Camellia seeds, is proved to be able to reduce the difficulty of aqueous extraction processing of Camellia seed oil. With the continuous accumulation of tea saponin by aqueous phase cyclic utilization, the interfacial tension between extracting agent and oil continuously decreases, which promotes the release of oil from raw materials and improves the utilization of protein and other by‐products simultaneously. This method fully embodies the concept of green extraction and has potential application value to the enterprises which have industrialized production of Camellia oil by alcohol‐assisted aqueous extraction processing. Abstract : Tea saponin (TS), which is rich in Camellia seeds, is proved to be able to reduce the difficulty of aqueous extraction processing of Camellia seed oil. With the continuous accumulation of tea saponin by aqueous phase cyclic utilization, the interfacial tension between extracting agent and oil continuously decreases, which promotes the release of oil from raw materials and improves the utilization of protein and other by‐products simultaneously. This method fully embodies the concept of green extraction and has potential application value to the enterprises which have industrialized production of Camellia oil by alcohol‐assisted aqueous extraction processing.